Estimating the changing burden of disease attributable to high body mass index in South Africa for 2000, 2006 and 2012 - Bradshaw, D; Joubert, J D; Abdelatief, N; Cois, A; Turawa, E B; Awotiwon, O F; Roomaney, R A; Neethling, I; Pacella, R; Pillay van-Wyk, V (South African Medical Journal, 2022)
Background. A high body mass index (BMI) is associated with several cardiovascular diseases, diabetes and chronic kidney disease, cancers, and other selected health conditions. Objectives. To quantify the deaths and disability-adjusted life years (DALYs) attributed to high BMI in persons aged ≥20 years in South Africa (SA) for 2000, 2006 and 2012. Methods. The comparative risk assessment (CRA) methodology was followed. Meta-regressions of the BMI mean and standard deviation from nine national surveys spanning 1998 - 2017 were conducted to provide estimates by age and sex for adults aged ≥20 years. Population attributable fractions were calculated for selected health outcomes using relative risks identified by the Global Burden of Disease Study (2017), and applied to deaths and DALY estimates from the second South African National Burden of Disease Study to estimate the burden attributed to high BMI in a customised Microsoft Excel workbook. Monte Carlo simulation-modelling techniques were used for the uncertainty analysis. BMI was assumed to follow a log-normal distribution, and the theoretical minimum value of BMI below which no risk was estimated was assumed to follow a uniform distribution from 20 kg/m2 to 25 kg/m2. Results. Between 2000 and 2012, mean BMI increased by 6% from 27.7 kg/m2 (95% confidence interval (CI) 27.6 - 27.9) to 29.4 kg/m2 (95% CI 29.3 - 29.5) for females, and by 3% from 23.9 kg/m2 (95% CI 23.7 - 24.1) to 24.6 kg/m2 (95% CI 24.5 - 24.8) for males. In 2012, high BMI caused 58 757 deaths (95% uncertainty interval (UI) 46 740 - 67 590) or 11.1% (95% UI 8.8 - 12.8) of all deaths, and 1.42 million DALYs (95% UI 1.15 - 1.61) or 6.9% (95% UI 5.6 - 7.8) of all DALYs. Over the study period, the burden in females was 1.5 - 1.8 times higher than that in males. Type 2 diabetes mellitus became the leading cause of death attributable to high BMI in 2012 (n=12 382 deaths), followed by hypertensive heart disease (n=12 146), haemorrhagic stroke (n=9 141), ischaemic heart disease (n=7 499) and ischaemic stroke (n=4 044). The age-standardised attributable DALY rate per 100 000 population for males increased by 6.6% from 3 777 (95% UI 2 639 - 4 869) in 2000 to 4 026 (95% UI 2 831 - 5 115) in 2012, while it increased by 7.8% for females from 6 042 (95% UI 5 064 - 6 702) to 6 513 (95% UI 5 597 - 7 033). Conclusion. Average BMI increased between 2000 and 2012 and accounted for a growing proportion of total deaths and DALYs. There is a need to develop, implement and evaluate comprehensive interventions to achieve lasting change in the determinants and impact of overweight and obesity, particularly among women.